The worship guitar book : the goods, the gear, and the gifting for the worship guitarist - Doppler, Doug. (Milwaukee, WI : Hal Leonard Books, 2013)
Learn how to get great sounds. Let Doug Doppler show you practice and rehearsal techniques that can mold you into an excellent guitarist and find ways to approach excellent music with a pure heart, ready to worship God. The Worship Guitar Book is written in five parts designed to help the worship team guitarist play better while at the same time functioning with a good personal and spiritual attitude. Doug Doppler sets the framework for a wonderful resource presented with a heart for people, God, and excellence in all things. Doppler sheds light on the importance of well-designed practice routines, music theory, and working with a team toward a shared intention of supporting a powerful worship experience for the church body. Follow the learning path from the why's and how's of worship, to musical considerations, to choosing gear, to rehearsal and performance techniques, and finally to team building, leadership dynamics, and evangelism."--
Includes bibliographical references and index.
Keywords: Guitar -- Instruction and study; Contemporary Christian music -- Instruction and study